Spatial and temporal variability of phytoplankton dynamics in-relation to essential oceanographic variables in the south east coast of Bangladesh - Sarker, Subrata; Riya, Shashowti; Rahman, Mohammad; Huda, A. N. M. Samiul; Hossain, Md. Shahadat; Das, Nabanita (Elsevier, 2023)
Phytoplankton form the base of food chain and play a key role in maintaining the global climate system. However, very limited knowledge is available about the phytoplankton ecology of Bangladesh coast which is a representation of sub-tropical coastal ecosystem. Thus, this study aimed to understand the spatial and temporal variability of phytoplankton community in-relation to environmental variables in the South East coast of Bangladesh. Monthly data on essential oceanographic variables (i.e. temperature, salinity, dissolved oxygen, turbidity, silicate, nitrate and phosphate) and phytoplankton species abundance were collected from January 2022 to December 2022. We found a strong spatial and temporal variability in essential oceanographic variables and phytoplankton community compositions in Naf – Saint Martin Peninsula of Bangladesh. Estuarine ecosystem is characterized by high nutrients and low salinity while offshore ecosystem was found with comparatively low nutrients and high salinity. About 154 phytoplankton species were identified from the study area through year round sampling events. In the estuarine ecosystem Skeletonema marino, Coscinodiscus centralis, Coscinodiscus argus and Coscinodiscus traducens were found as the major contributing species at the estuarine ecosystem while Chaetoceros radican, Tripos trichoceros, Cylindrotheca Closterium, Chaetoceros convulutus, Tripos muelleri, and Cyclotella striata were found as the major contributing species at the offshore ecosystem. Our study found that 6 explanatory variables (i.e. temperature, salinity, turbidity, silicate, nitrate and phosphate) jointly explained about 78% variability in phytoplankton community dynamics. Nitrate concentration explained maximum variability (19%) followed by phosphate (17%), salinity (15%), silicate (12%), turbidity (10%) and surface temperature (5%). This study will play a key role in understanding the spatial and temporal variability of phytoplankton dynamics in the sub-tropical coastal ecosystem.